Global transcriptional regulator FNR regulates the pyruvate cycle and proton motive force to play a role in aminoglycosides resistance of Edwardsiella tarda - Mao, Li-Chun; Li, Shao-Hua; Peng, Xuan-Xian; Li, Hui (Frontiers in Microbiology, 2022)
Bacterial metabolism is related to resistance and susceptibility to antibiotics. Fumarate and nitrate reduction regulatory protein (FNR) is a global transcriptional regulator that regulates metabolism. However, the role of FNR in antibiotic resistance is elusive. Here, fnr deletion mutant was constructed and used to test the role in Edwardsiella tarda EIB202 (EIB202). △fnr exhibited elevated sensitivity to aminoglycosides. The mutant had a globally enhanced metabolome, with activated alanine, aspartate and glutamate metabolism and increased abundance of glutamic acid as the most impacted pathway and crucial biomarker, respectively. Glutamate provides a source for the pyruvate cycle (the P cycle) and thereby relationship between exogenous glutamate-activated P cycle and gentamicin-mediated killing was investigated. The activated P cycle elevated proton motive force (PMF). Consistently, exogenous glutamate potentiated gentamicin- mediated killing to EIB202 as the similarity as the loss of FNR did. These finding reveal a previously unknown regulation by which FNR downregulates glutamate and in turn inactivates the P cycle, which inhibits PMF and thereby exhibits the resistance to aminoglycosides.